Cocrystal high-entropy alloy, preparation method and application, and heat-treatment-free laser additive repair method for metal parts
Patent Information
- Application Number
- CN202411015233.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-07-25
AI Technical Summary
但是被修复工件基体在该工件基体制备过程中已经过一次固溶和时效热处理,再次随修复层进行热处理会造成基体晶粒的长大,显著降低基体性能
[0022]具体的,本发明提供的共晶高熵合金利用高熵化与双相协同强韧化机制,代替传统合金固相反应析出强化,同时利用激光增材制造技术的强热梯度和高冷却速率的非平衡加工条件,制备出纳米层状结构,结合细晶强化来实现性能兼容与免热处理性。其中本发明所述共晶高熵合金在没有添加贵重金属元素的情况下,利用微观组织调控,即共晶高熵合金独特的超细双相片层组织,软硬两相兼具了面心立方和体心立方高熵合金的强度和塑性的优势,且随服役时间和服役温度增加,组织中无新相的萌生和片层双相的显著退化,该共晶高熵合金打印态的室温拉伸强度明显优于GH4169打印态,且该共晶高熵合金打印态无需热处理即可使材料达到GH4169锻件标准热处理态室温力学性能水平,实现同种服役工况条件下低成本、低密度替代。
Smart Images

Figure CN118932236B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy materials technology, and in particular to eutectic high-entropy alloys, their preparation methods and applications, and a laser additive repair method for metal parts without heat treatment. Background Technology
[0002] During the service life of high-temperature alloy components in aerospace, power, energy, and chemical industries, some critical components may develop defects such as cracks due to deformation, wear, and corrosion. This can have a serious negative impact on the safety and efficiency of the equipment. These components have high performance requirements and are generally expensive. If surface damage can be effectively repaired to restore and improve their performance, the normal operation of the equipment can be effectively guaranteed, production costs can be reduced, and significant economic benefits can be achieved.
[0003] Laser additive repair is an advanced remanufacturing technology that uses a high-power laser beam as an energy source to repair locally damaged parts. This technology has the characteristics of high repair accuracy, high efficiency, small heat-affected zone, minimal workpiece damage, good microstructure and properties of the repaired area, and high material utilization. Because it can form near-size parts, it has significant technical advantages in ensuring the geometric accuracy of repaired scrap products or parts, and is one of the feasible technologies for repairing hot-end high-temperature alloy parts.
[0004] However, the high-temperature strength of high-temperature alloys is often achieved through solid-state phase transformation precipitation strengthening phases. Therefore, using high-temperature alloy powder for repair technology requires heat treatment to achieve tempering and performance targets. Furthermore, the heat treatment process can also adversely affect the repaired object. Currently, alloy materials used for component repair typically require heat treatment to control precipitates and grain size to optimize and improve performance. Taking GH4169 alloy as an example, the microstructure of the laser additive GH4169 repair layer mainly consists of columnar dendrites and equiaxed dendrites, with significant elemental segregation between dendrites. It is mainly enriched in Nb and Mo, and depleted in Fe, Cr, and Ni. The repair layer mainly consists of the matrix γ phase, Laves phase, MC carbide, and MN nitride. High-temperature solution treatment and aging are necessary to effectively refine the grains and eliminate the Laves segregation phase, thereby effectively improving the mechanical properties of the repair layer. However, the substrate of the workpiece being repaired has already undergone solution treatment and aging heat treatment during the preparation of the workpiece substrate. If it is heat treated again along with the repair layer, it will cause the substrate grains to grow, which will significantly reduce the substrate performance.
[0005] Eutectic alloys are materials whose main strengthening mechanism is eutectic precipitation. They are two-phase structures that are formed directly during solidification and generally do not require heat treatment to control and optimize, resulting in precipitation and interfacial strengthening. However, it is generally difficult to balance high-temperature strength, high-temperature thermal stability and additive manufacturing applicability in these materials. Summary of the Invention
[0006] The purpose of this invention is to provide a eutectic high-entropy alloy, its preparation method and application, and a method for laser additive repair of metal parts without heat treatment. The eutectic high-entropy alloy provided by this invention can be used in the laser additive repair of metal parts, and good repair effect can be guaranteed without heat treatment.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0008] This invention provides a eutectic high-entropy alloy, the elemental composition of which, by mass percentage, includes: Co 20-24%, Al 9-11%, Fe 20-24%, Hf 0.5-5%, Y 0.005-1%, C 0.005-1%, B 0.005-1%, and Ni balance.
[0009] This invention provides a method for preparing the eutectic high-entropy alloy described above, comprising the following steps:
[0010] The raw materials are prepared according to the elemental composition of the eutectic high-entropy alloy and then smelted. The resulting alloy liquid is then subjected to gas atomization treatment to obtain the eutectic high-entropy alloy.
[0011] Preferably, the melting is carried out under a vacuum of 5×10⁻⁶. -3 ~1×10 -4 Performed under MPa conditions;
[0012] The conditions for the atomization process include: the protective gas used is an inert gas, the diameter of the nozzle used is 4 mm, the atomization pressure is 4–10 MPa, and the atomization time is 5–15 min.
[0013] This invention provides the application of the eutectic high-entropy alloy described in the above technical solution or the eutectic high-entropy alloy prepared by the preparation method described in the above technical solution in the heat-free laser additive repair of metal parts.
[0014] Preferably, the metal parts are made of high-temperature alloys; the laser additive repair method includes laser selective melting forming repair or laser coaxial powder feeding repair.
[0015] This invention provides a method for heat-free laser additive repair of metal parts, comprising the following steps:
[0016] Using the eutectic high-entropy alloy described in the above technical solution or the eutectic high-entropy alloy prepared by the preparation method described in the above technical solution as the repair material, laser additive repair is performed on the metal parts to be repaired.
[0017] Preferably, the metal parts to be repaired are made of high-temperature alloys; the laser additive repair method includes laser selective melting forming repair or laser coaxial powder feeding repair.
[0018] Preferably, the conditions for laser selective melting and forming repair include: the particle size of the eutectic high-entropy alloy used is 15-53 μm; the laser power is 215-335 W, the scanning rate is 800-1100 mm / s, the powder layer thickness is 30-60 μm, the scanning interval is 80-120 μm; the scanning method is strip scanning, and the layer is rotated 67° after each layer is scanned.
[0019] Preferably, the conditions for laser coaxial powder feeding repair include: the particle size of the eutectic high-entropy alloy used is 53-150 μm; the laser power is 1800-2200 W, the scanning rate is 720-960 mm / s, the powder feeding amount is 12-14 g / min, the overlap width is 1-1.6 mm, the spot diameter is 0.5-3 mm, and the interlayer dwell time is 30-60 s.
[0020] Preferably, the repair material is obtained directly without heat treatment after the laser additive repair is completed, and the repair material has a nano-layered eutectic two-phase structure.
[0021] Beneficial Effects: This invention utilizes the design and thermal stability of eutectic high-entropy alloy composition, the microstructure construction and low-defect process of additive manufacturing, and process optimization for heat-free repair. It provides a eutectic high-entropy alloy and its preparation method, as well as a heat-free laser additive repair method for metal parts, solving the problem of efficient and high-performance heat-free repair of metal parts. Specifically, this invention provides a eutectic high-entropy alloy, whose elemental composition, by mass percentage, includes: Co 20-24%, Al 9-11%, Fe 20-24%, Hf 0.5-5%, Y 0.005-1%, C 0.005-1%, B 0.005-1%, and Ni as the balance. This invention, by controlling the proportion of main elements and the content of trace elements such as Hf, utilizes the multi-principal high-entropy effect and high Hf and C strengthening design to enable eutectic high-entropy alloys to have good thermal stability. Using this alloy as a repair material and employing laser additive manufacturing technology, successful repair of metal parts can be achieved without heat treatment. The resulting repair material has a nano-layered eutectic two-phase structure and possesses mechanical properties comparable to high-temperature alloys without additional heat treatment. This solves the problem of secondary damage to the matrix material properties caused by heat treatment after traditional additive repair, and is suitable for efficient and high-performance repair of thermally sensitive high-temperature alloy metal parts.
[0022] Specifically, the eutectic high-entropy alloy provided by this invention utilizes a high-entropy and dual-phase synergistic strengthening mechanism to replace the solid-state reaction precipitation strengthening of traditional alloys. Simultaneously, it leverages the strong thermal gradient and high cooling rate of non-equilibrium processing conditions in laser additive manufacturing technology to prepare a nano-layered structure, combining fine-grain strengthening to achieve performance compatibility and heat treatment-free operation. The eutectic high-entropy alloy of this invention, without the addition of precious metal elements, utilizes microstructure control—specifically, the unique ultrafine dual-phase lamellar structure of the eutectic high-entropy alloy—combining the strength and plasticity advantages of both face-centered cubic and body-centered cubic high-entropy alloys. Furthermore, with increasing service time and temperature, there is no initiation of new phases and significant degradation of the lamellar dual phases. The room-temperature tensile strength of the printed state of this eutectic high-entropy alloy is significantly superior to that of the GH4169 printed state. Moreover, the printed state of this eutectic high-entropy alloy can achieve the room-temperature mechanical properties of the standard heat-treated state of GH4169 forgings without heat treatment, realizing a low-cost, low-density replacement under the same service conditions. Attached Figure Description
[0023] Figure 1 SEM images of the alloy powder with a particle size of 15–53 μm prepared in Example 1;
[0024] Figure 2 These are photographs of printed samples 1-10 from Example 2;
[0025] Figure 3 SEM images of printed samples 1-10 in Example 2;
[0026] Figure 4 The room temperature tensile stress-strain curves of printed specimens 1-10 in Example 2;
[0027] Figure 5 This is a schematic diagram of the observation plane for the sample tissue.
[0028] Figure 6 SEM images of printed samples 1-10;
[0029] Figure 7 SEM images of printed samples 1-10 after heat treatment at 600℃ for 6 hours;
[0030] Figure 8 SEM images of printed samples 1-10 after heat treatment at 700℃ for 6 hours;
[0031] Figure 9 SEM images of printed samples 1-10 after heat treatment at 800℃ for 6 hours;
[0032] Figure 10 SEM images of printed samples 1-10 after heat treatment at 900℃ for 6 hours;
[0033] Figure 11 SEM images of printed samples 1-10 after being kept at 1000℃ for 6 hours;
[0034] Figure 12 SEM images of printed samples 1-10 after heat treatment at 1300℃ for 2 hours;
[0035] Figure 13 A photograph of the repaired sample in Example 3;
[0036] Figure 14 This is a SEM image of the repaired sample in Example 3. Detailed Implementation
[0037] This invention provides a eutectic high-entropy alloy, the elemental composition of which, by mass percentage, includes: Co 20-24%, Al 9-11%, Fe 20-24%, Hf 0.5-5%, Y 0.005-1%, C 0.005-1%, B 0.005-1%, and Ni balance.
[0038] The elemental composition of the eutectic high-entropy alloy provided by this invention, by mass percentage, includes: Co 20-24%, specifically 20%, 21%, 22%, 23%, or 24%; Al 9-11%, specifically 9%, 9.5%, 10%, 10.5%, or 11%; Fe 20-24%, specifically 20%, 21%, 22%, 23%, or 24%; Hf 0.5-5%, specifically 0.5%, 1%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%; Y 0.005-1%, specifically 0.005%, 0.01%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, or 1%; C The content of C, B, and Hf in the eutectic high-entropy alloy is 0.005% to 1%, specifically 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%; the content of B is 0.005% to 1%, specifically 0.005%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%; and the balance is Ni. This invention controls the elements (where C, B, and Hf are grain boundary strengthening elements) in the eutectic high-entropy alloy within the above ranges. By using the eutectic high-entropy alloy in laser additive repair of metal parts, good repair results can be guaranteed without heat treatment. In this invention, the eutectic high-entropy alloy is specifically a powder material, and the particle size of the eutectic high-entropy alloy is preferably 15-150 μm (specifically, it can be 15-53 μm or 53-150 μm). In practical applications, the required particle size of the eutectic high-entropy alloy can be obtained by sieving according to specific process requirements. By controlling the proportion of the main elements and the content of trace elements such as Hf, this invention can make the eutectic high-entropy alloy have good thermal stability. Using it as a repair material and utilizing laser additive manufacturing technology, successful repair of metal parts can be achieved without heat treatment.
[0039] This invention provides a method for preparing the eutectic high-entropy alloy described above, comprising the following steps:
[0040] The raw materials are prepared according to the elemental composition of the eutectic high-entropy alloy and then smelted. The resulting alloy liquid is then subjected to gas atomization treatment to obtain the eutectic high-entropy alloy.
[0041] This invention involves preparing raw materials according to the elemental composition of the eutectic high-entropy alloy, followed by melting to obtain an alloy liquid. This invention does not specifically limit the raw materials used; any raw materials well-known to those skilled in the art (e.g., alloys) can be used, as long as the elemental composition of the final product meets the above requirements. In this invention, the melting is preferably carried out under a vacuum of 5 × 10⁻⁶. -3 ~1×10 -4 The vacuum degree is preferably 6 × 10 MPa. -3 MPa. The smelting is preferably carried out in a smelting furnace.
[0042] After obtaining the alloy liquid, the present invention performs gas atomization treatment on the alloy liquid to obtain the eutectic high-entropy alloy. In the present invention, the conditions for the gas atomization treatment include: the protective gas used is preferably an inert gas, the inert gas is preferably argon, and the purity of the argon is preferably 99.9%; the diameter of the nozzle used is preferably 4 mm, and the nozzle is preferably a graphite nozzle; the gas atomization pressure is preferably 4-10 MPa, more preferably 8 MPa; the gas atomization treatment time is preferably 5-15 min, more preferably 12 min. The present invention preferably sprays the alloy liquid into an atomization tower through a nozzle, and performs the gas atomization treatment in the presence of an inert gas; by adjusting the gas atomization pressure, the alloy liquid is broken up by the inert gas and cooled to obtain a powdered eutectic high-entropy alloy.
[0043] After the gas atomization treatment, the present invention preferably obtains the required particle size of the eutectic high-entropy alloy by sieving according to specific process requirements; the equipment used for sieving is preferably a powder sieving machine.
[0044] This invention provides the application of the eutectic high-entropy alloy described in the above-described technical solution or the eutectic high-entropy alloy prepared by the above-described preparation method in heat-free laser additive repair of metal parts. In this invention, the material of the metal parts is preferably a high-temperature alloy, and the high-temperature alloy preferably includes a nickel-based high-temperature alloy or a high-entropy alloy; the laser additive repair method preferably includes laser selective melting forming repair or laser coaxial powder feeding repair.
[0045] This invention innovatively utilizes the eutectic precipitation theory, which states that a two-phase structure can be formed during solidification, or a two-phase structure with potential precipitation and interface strengthening effects can be provided under heat treatment-free conditions. Since the target object for repair is a high-temperature alloy, the repair material needs to have high-temperature strength; therefore, high-entropy thermal strengthening is chosen. Combining eutectic behavior, this invention cleverly utilizes eutectic high-entropy alloys and additive manufacturing to solve the problem of repairing high-temperature alloy parts. This relies on creative work in areas such as the design and thermal stability of eutectic high-entropy alloy composition, the microstructure construction and low-defect process of additive manufacturing, and process optimization for heat treatment-free applications. Specifically, the powdered eutectic high-entropy alloy provided by this invention, as a repair material, can form samples with high density and no macroscopic cracks using both laser selective melting and laser coaxial powder feeding repair processes. This invention ingeniously utilizes a combination of methods, including the high entropy effect of multiple principal elements, in-situ generation of eutectic biphase structures, and the fabrication of nanolayered structures through laser additive manufacturing. By synergistically combining composition and process, a material repair technology has been developed that achieves "one-step manufacturing" by constructing a multi-scale structure encompassing "atomic stability, microstructure, and mesostructure." Without heat treatment, its performance is comparable to classic high-temperature alloys such as GH4169. The heat-free feature solves the problem of secondary damage to the base material properties caused by heat treatment after additive manufacturing. It is suitable for efficient and high-performance repair of high-temperature alloy metal parts sensitive to heat treatment processes, and the implementation process is relatively simple, making it suitable for widespread application.
[0046] This invention provides a method for heat-free laser additive repair of metal parts, comprising the following steps:
[0047] Using the eutectic high-entropy alloy described in the above technical solution or the eutectic high-entropy alloy prepared by the preparation method described in the above technical solution as the repair material, laser additive repair is performed on the metal parts to be repaired.
[0048] In this invention, the material of the metal parts to be repaired is preferably a high-temperature alloy, and the high-temperature alloy preferably includes a nickel-based high-temperature alloy or a high-entropy alloy; the laser additive repair method preferably includes laser selective melting and forming repair or laser coaxial powder feeding repair, which will be described in detail below.
[0049] In this invention, the substrate used for laser selective melting and forming repair is preferably a 304 stainless steel substrate. Preferably, the substrate is preheated before laser selective melting and forming repair, and the preheating temperature is preferably 80–130°C, more preferably 95°C. In this invention, the substrate preferably undergoes surface treatment before preheating. The surface treatment preferably includes: pre-blasting the upper surface of the substrate with a sandblasting machine, cleaning with acetone to remove surface impurities, then cleaning with alcohol, and drying.
[0050] In this invention, the eutectic high-entropy alloy used for laser selective melting and forming repair is dried before use, preferably under vacuum conditions; the drying temperature is preferably 120-150°C, more preferably 130°C; and the drying time is preferably 1-3 hours, more preferably 2 hours.
[0051] In this invention, the conditions for laser selective melting and forming repair include: the particle size of the eutectic high-entropy alloy used is preferably 15–53 μm; the laser power is preferably 215–335 W, more preferably 245–305 W, and even more preferably 275 W; the scanning rate is preferably 800–1100 mm / s, and even more preferably 900–1000 mm / s; the powder layer thickness is preferably 30–60 μm, and even more preferably 40 μm; the scanning spacing is preferably 80–120 μm, and even more preferably 100 μm; the scanning method is strip scanning, and after each layer is scanned, the layer is rotated 67° to ensure that the scanning direction is completely repeated after multiple layers are processed, thereby reducing the accumulation of residual stress. This invention preferably optimizes laser selective melting and forming repair under the above conditions, which is beneficial for improving the compactness of the eutectic high-entropy alloy, while reducing the residual stress inside the eutectic high-entropy alloy, avoiding the formation of cracks in the alloy, and the resulting eutectic high-entropy alloy has good mechanical properties without subsequent processing (such as heat treatment).
[0052] In this invention, the laser selective melting and forming repair is preferably performed in a protective atmosphere, preferably argon, with a purity preferably ≥99.99%; the oxygen content in the protective atmosphere is preferably <400ppm, more preferably <350ppm. This preferred method of performing laser selective melting and forming repair in a protective atmosphere prevents the powdered eutectic high-entropy alloy from undergoing an oxidation reaction with oxygen in the air.
[0053] This invention utilizes laser selective melting technology to rapidly process and shape eutectic high-entropy alloys using a focused laser beam, resulting in near-dense components. Simultaneously, the ultra-fast cooling rate can, to some extent, prevent the formation of brittle intermetallic compounds and elemental segregation, thereby obtaining eutectic high-entropy alloy components with refined microstructure and uniform composition. Furthermore, laser selective melting technology is not constrained by the complex shape of the formed part, enabling the production of complex-shaped components with high surface precision. This effectively improves production efficiency, reduces production costs, and broadens the application fields of eutectic high-entropy alloys.
[0054] In this invention, the eutectic high-entropy alloy used for laser coaxial powder delivery repair is dried before use, preferably under vacuum conditions; the drying temperature is preferably 120-150°C, more preferably 130°C; and the drying time is preferably 1-3 hours, more preferably 2 hours.
[0055] In an embodiment of the present invention, the metal parts to be repaired for laser coaxial powder feeding repair are DD432 single crystal alloy cylinders that have undergone standard heat treatment. The cylinder diameter is 15mm. The cross-section is pre-polished with sandpaper to a bright mirror surface, then cleaned with ethanol, dried, and finally the metal parts to be repaired are placed stably on the forming platform.
[0056] In this invention, the conditions for laser coaxial powder feeding repair include: the particle size of the eutectic high-entropy alloy used is preferably 53-150 μm; the laser power is preferably 1800-2200 W, more preferably 2000 W; the scanning rate is preferably 720-960 mm / s, more preferably 840 mm / s; the powder feeding amount is preferably 12-14 g / min, more preferably 13.3 g / min; the overlap width is preferably 1-1.6 mm, more preferably 1.4 mm; the spot diameter is preferably 0.5-3 mm, more preferably 2 mm; and the interlayer dwell time is preferably 30-60 s, more preferably 40 s. This invention chooses to add an interlayer dwell time, which is beneficial to ensuring that each layer of cladding repair has a good effect. The present invention preferably performs laser coaxial powder feeding repair under the above conditions, which is beneficial to improve the compactness of the eutectic high-entropy alloy, while reducing the residual stress inside the eutectic high-entropy alloy, avoiding the formation of cracks in the alloy, enhancing the interfacial bonding strength between the matrix (i.e. the metal parts to be repaired) and the repaired part, resulting in good interfacial bonding effect. The repaired part (i.e. the repaired metal parts) does not require subsequent processing (such as heat treatment) and has good mechanical properties.
[0057] In this invention, the laser coaxial powder feeding repair is preferably performed in a protective atmosphere, preferably argon, with a purity preferably ≥99.99%; the oxygen content in the protective atmosphere is preferably <400ppm, more preferably <350ppm. This invention preferably uses a protective atmosphere for laser coaxial powder feeding repair to achieve epitaxial growth, which can prevent the powdered eutectic high-entropy alloy from undergoing oxidation with oxygen in the air.
[0058] In this invention, the repair material is obtained directly without heat treatment after the laser additive repair is completed, and the repair material has a nano-layered eutectic two-phase structure.
[0059] In this invention, the high-entropy alloy differs from the design principles of traditional alloys, exhibiting a multi-principal-element high-entropy effect. Although there are many principal elements, they form a solid solution structure, resulting in superior mechanical properties such as high hardness, high wear resistance, and high strength compared to traditional alloys. Furthermore, through the rational blending of elements, a eutectic high-entropy alloy can be designed, enabling the in-situ formation of a two-phase structure. This achieves a dual-phase structure that combines excellent plasticity (face-centered cubic) with high strength (body-centered cubic), resulting in a superior balance between strength and plasticity. Simultaneously, advanced laser additive manufacturing processes can utilize non-equilibrium processing conditions with strong thermal gradients and high cooling rates to prepare nanolayered structures, significantly enhancing the synergistic strengthening effect of the eutectic high-entropy alloy. Combining these advantages, the eutectic high-entropy alloy provided by this invention can generate a multiphase structure of nanosheets through a eutectic reaction during solidification, eliminating the need for heat treatment to achieve two-phase / multiphase control through solid-state phase transformation precipitation. Applying the eutectic high-entropy alloy provided by this invention to laser additive repair of metal parts ensures good repair results without heat treatment.
[0060] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0061] Example 1
[0062] The composition of the eutectic high-entropy alloy in this embodiment, by mass percentage, is as follows: Co 23%, Al 10%, Fe 22%, Hf 2%, Y 0.1%, C 0.5%, B 0.5%, and Ni balance;
[0063] According to the composition of the eutectic high-entropy alloy, the resulting mixed raw materials were placed in a melting furnace and evacuated to a vacuum of 6 × 10⁻⁶. -3 At MPa, the alloy liquid was obtained by smelting.
[0064] The alloy liquid was sprayed into the atomization tower using a graphite nozzle with a diameter of 4 mm. Argon gas with a purity of 99.9% was introduced as a protective gas. The atomization was carried out for 12 minutes under a gas atomization pressure of 8 MPa. During the atomization process, the alloy liquid was broken up and cooled by argon gas to obtain alloy powder.
[0065] The alloy powder was sieved using a powder sieve to obtain alloy powder with a particle size of 15-53 μm (which will be used for laser selective melting and forming repair process) and alloy powder with a particle size of 53-150 μm (which will be used for laser coaxial powder feeding repair process).
[0066] Figure 1The image shows an SEM image of the alloy powder with a particle size of 15–53 μm prepared in Example 1. The results show that the alloy powder has a uniform particle size.
[0067] Example 2
[0068] The alloy powder with a particle size of 15–53 μm prepared in Example 1 was used as a eutectic high-entropy alloy powder for laser additive repair without heat treatment to conduct experiments on laser selective melting forming repair process, as detailed below:
[0069] The alloy powder with a particle size of 15-53 μm prepared in Example 1 was placed in a drying oven and heated to 130°C in a vacuum environment for 2 hours. After that, it was cooled with the oven and the resulting dried alloy powder was added to the powder feeding cylinder of the laser selective melting equipment.
[0070] The forming substrate is made of 304 stainless steel. The upper surface of the forming substrate is sandblasted with a sandblasting machine and cleaned with acetone to remove surface impurities. Then it is cleaned with ethanol, dried, and the dried forming substrate is installed on the forming platform and leveled. Then it is preheated to 95°C.
[0071] Turn on the laser selective melting forming equipment and set the printing parameters: laser power, scanning speed, scanning spacing and powder layer thickness are shown in Table 1. Under the protection of high-purity argon gas (argon purity ≥99.99%, oxygen content <350ppm), laser selective melting forming repair is carried out in a closed chamber. The scanning method is strip scanning, and after each layer is scanned, the sample is rotated 67° to obtain a eutectic high-entropy alloy printed sample.
[0072] Table 1 SLM process parameters
[0073]
[0074] Based on Table 1, the optimal process parameters were determined to be: laser power of 275W, scanning speed of 1000mm / s, scanning spacing of 0.1mm, and powder layer thickness of 0.04mm. Photographs of the eutectic high-entropy alloy printed samples (denoted as printed samples 1-10) prepared under these optimal process parameters are shown below. Figure 2 As shown.
[0075] Microstructure observation and mechanical property testing were performed on printed samples 1-10, as detailed below:
[0076] Figure 3 The SEM images of the printed samples 1-10 in Example 2 show that the microstructure of the printed samples 1-10 is an extremely fine two-phase eutectic structure (the density of the printed samples 1-10 is >99%).
[0077] Figure 4Table 2 shows the room temperature tensile stress-strain curves of the printed specimens 1-10 in Example 2. The mechanical properties of the printed specimens 1-10, the GH4169 printed specimens, and the GH4169 forging in its standard heat-treated state are compared. The results show that the room temperature tensile mechanical properties of the printed specimens 1-10 provided by this invention are excellent, significantly better than those of the GH4169 printed specimens, and can reach the room temperature tensile mechanical property level of the GH4169 forging in its standard heat-treated state without heat treatment.
[0078] Table 2 Mechanical properties of printed specimens 1-10, GH4169 printed specimens, and GH4169 forgings in standard heat-treated state.
[0079]
[0080] The printed samples 1-10 were incubated at 600℃, 700℃, 800℃, 900℃, and 1000℃ for 6 hours, and at 1300℃ for 2 hours, respectively. The tissue changes were observed, as follows:
[0081] Figure 5 This is a schematic diagram of the plane for observing the sample tissue. The tissue being observed is in a plane perpendicular to the printing direction.
[0082] Figure 6 The images show SEM images of printed samples 1-10. The left image shows a longitudinal section of rod-shaped tissue, while the right image shows a cross section of rod-shaped tissue. The results indicate that the BCC phase presents as a fishbone-shaped short rod structure.
[0083] Figure 7 The images show SEM images of printed samples 1-10 after being kept at 600℃ for 6 hours. The left image shows a longitudinal section of rod-shaped tissue, while the right image shows a cross section of rod-shaped tissue. The results show that a few rod-shaped BCCs are connected.
[0084] Figure 8 The images show SEM images of printed samples 1-10 after being kept at 700℃ for 6 hours. The left image shows a longitudinal section of rod-shaped tissue, while the right image shows a cross section of rod-shaped tissue. The results show that most of the rod-shaped BCCs are connected to form lamellar tissue.
[0085] Figure 9 The images show SEM images of printed samples 1-10 after being kept at 800℃ for 6 hours. The left image shows a longitudinal section of lamellar tissue, while the right image shows a cross section of lamellar tissue. The results show that the rod-shaped BCC phases are all connected to form lamellar tissue.
[0086] Figure 10The SEM images of printed samples 1-10 after being kept at 900℃ for 6 hours show that the BCC layers are interconnected to form a labyrinthine lamellar structure.
[0087] Figure 11 The SEM images of printed samples 1-10 after being kept at 1000℃ for 6 hours show that the BCC layers of the sheets have interconnected and grown.
[0088] Figure 12 The SEM images of printed samples 1-10 after being kept at 1300℃ for 2 hours show that the two-phase lamellar structures merged to form large lamellar structures at high temperature, and the two phases remained stable.
[0089] Depend on Figures 6-12 It can be seen that the eutectic high-entropy alloy provided by the present invention has good microstructure stability and overheat resistance. As the service temperature increases, there is no initiation of new phases and no significant degradation of lamellar biphase in the microstructure.
[0090] Example 3
[0091] The alloy powder with a particle size of 53–150 μm prepared in Example 1 was used as a eutectic high-entropy alloy powder for laser additive repair without heat treatment to conduct experiments on laser coaxial powder feeding repair process, as detailed below:
[0092] The alloy powder with a particle size of 53-150 μm prepared in Example 1 was placed in a drying oven and heated to 130°C in a vacuum environment for 2 hours. After that, it was cooled with the oven and the resulting dried alloy powder was added to the powder feeding cylinder of the laser coaxial powder feeding device.
[0093] The metal parts to be repaired are DD432 single crystal alloy cylinders that have undergone standard heat treatment. The cylinder diameter is 15mm. The cross-section is first polished with sandpaper to a bright mirror surface, then cleaned with ethanol, dried, and the dried metal parts to be repaired are placed stably on the forming platform.
[0094] Turn on the laser coaxial powder feeding device and set the printing parameters: spot diameter is 2mm, powder feeding rate is 13.3g / min, overlap width is 1.4mm, laser power is 2000W, scanning rate is 840mm / s, and interlayer dwell time is 40s; coaxial powder feeding repair is carried out in a closed chamber under the protection of high-purity argon gas (argon purity ≥99.99%, oxygen content <350ppm) to obtain the repaired sample.
[0095] The repaired sample was visually inspected, and the repair interface was examined using metallographic structure. Figure 13 This is a photograph of the repaired sample from Example 3. Figure 14 This is a SEM image of the repaired sample from Example 3; Figure 13 and Figure 14It can be seen that no cracks were found in the repaired sample.
[0096] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A eutectic high-entropy alloy, characterized in that, The elemental composition, by mass percentage, includes: Co 20-24%, Al 9-11%, Fe 20-24%, Hf 2-5%, Y 0.005-0.1%, C 0.5-1%, B 0.5-1%, and Ni balance; The eutectic high-entropy alloy is used as a repair material for laser additive repair of the metal parts to be repaired. The laser additive repair is a heat-free laser additive repair, and the laser additive repair method is laser selective melting forming repair or laser coaxial powder feeding repair. The conditions for laser selective melting and forming repair include: the particle size of the eutectic high-entropy alloy used is 15~53μm; the laser power is 215~335W, the scanning rate is 800~1100mm / s, the powder layer thickness is 30~60μm, the scanning interval is 80~120μm; the scanning method is strip scanning, and the layer is rotated 67° after each layer is scanned. The conditions for laser coaxial powder feeding repair include: the particle size of the eutectic high-entropy alloy used is 53~150μm; the laser power is 1800~2200W, the scanning rate is 720~960mm / s, the powder feeding amount is 12~14g / min, the overlap width is 1~1.6mm, the spot diameter is 0.5~3mm, and the interlayer dwell time is 30~60s.
2. The method for preparing the eutectic high-entropy alloy according to claim 1, characterized in that, Includes the following steps: The raw materials are prepared according to the elemental composition of the eutectic high-entropy alloy and then smelted. The resulting alloy liquid is then subjected to gas atomization treatment to obtain the eutectic high-entropy alloy.
3. The preparation method according to claim 2, characterized in that, The melting was carried out under a vacuum of 5×10⁻⁶. -3 ~1×10 - 4 Performed under MPa conditions; The conditions for the atomization process include: the protective gas used is an inert gas, the diameter of the nozzle used is 4 mm, the atomization pressure is 4~10 MPa, and the atomization time is 5~15 min.
4. The application of the eutectic high-entropy alloy of claim 1 or the eutectic high-entropy alloy prepared by the preparation method of claim 2 or 3 in the heat-free laser additive repair of metal parts.
5. The application according to claim 4, characterized in that, The metal parts are made of high-temperature alloys; the laser additive repair methods include laser selective melting forming repair or laser coaxial powder feeding repair.
6. A method for heat-free laser additive repair of metal parts, comprising the following steps: Using the eutectic high-entropy alloy of claim 1 or the eutectic high-entropy alloy prepared by the preparation method of claim 2 or 3 as the repair material, laser additive repair is performed on the metal parts to be repaired.
7. The method for heat-free laser additive repair of metal parts according to claim 6, characterized in that, The metal parts to be repaired are made of high-temperature alloys; the laser additive repair methods include laser selective melting forming repair or laser coaxial powder feeding repair.
8. The method for heat-free laser additive repair of metal parts according to claim 7, characterized in that, The conditions for laser selective melting and forming repair include: the particle size of the eutectic high-entropy alloy used is 15~53μm; the laser power is 215~335W, the scanning rate is 800~1100mm / s, the powder layer thickness is 30~60μm, the scanning interval is 80~120μm; the scanning method is strip scanning, and the laser is rotated 67° after each layer is scanned.
9. The method for heat-free laser additive repair of metal parts according to claim 7, characterized in that, The conditions for laser coaxial powder feeding repair include: the particle size of the eutectic high-entropy alloy used is 53~150μm; the laser power is 1800~2200W, the scanning rate is 720~960mm / s, the powder feeding amount is 12~14g / min, the overlap width is 1~1.6mm, the spot diameter is 0.5~3mm, and the interlayer dwell time is 30~60s.
10. The method for heat-free laser additive repair of metal parts according to any one of claims 6 to 9, characterized in that, The repair material is obtained directly without heat treatment after the laser additive repair is completed, and the repair material has a nano-layered eutectic two-phase structure.
Citation Information
Patent Citations
Light-weight high-entropy alloy and manufacturing process of impeller made of light-weight high-entropy alloys
CN110396634A
High-nickel eutectic high-entropy alloy powder for additive manufacturing and preparation method of high-nickel eutectic high-entropy alloy powder
CN111519078A
Double-phase high-entropy high-temperature alloy and additive manufacturing method thereof
CN113215468A
Complex-shape structural part formed through additive manufacturing and containing high-entropy alloy
CN114643362A